Cytogenetic and molecular characterization of almond trees treated with plant biostimulants or boron-based fertilizers - Esteves, Ana (2022)
Almond is highly produced in the NE of Portugal, where late frosts during flowering, low precipitation, and high tempera- ture in summer affect productivity and quality. Despite the use of late-flowering cultivars, plant biostimulants (PBs) and boron-based fertilizers can also be used to improve cell division, vegetative growth, photoassimilates rate, and nutritional status. PBs are widely used in some food crops, but the evaluation of their effects is still scarce. We treated three-year- old almond trees of cv. ‘Vairo,’ growing in a rainfed orchard in the NE of Portugal, with four individual treatments: two PBs (based on seaweed extract and free amino acids) and two boron-based fertilizers (applied on soil and leaves). Three monthly applications of seaweed extract (AN), free amino acids (AA), and boron ethanolamine (BE) were made. A single application of boron on the soil (BS) was made. Leaf samples were collected in treated and untreated (control) trees in cytogenetic and molecular analyses through the summer of 2019. The mitotic cell cycle analysis was performed to prepare mesophyll dividing cells stained with silver nitrate, and the molecular stability was assessed with five marker systems. This work aimed to extrapolate which individual treatment conferred higher mitotic cell cycle regularity and molecular stability. The cytogenetic and molecular data achieved in the cv. ‘Vairo,’ under the edaphoclimatic conditions studied, revealed that the individual treatments AA, BE, or BS induced higher leaf mitotic indexes, regular mitosis, and molecular stability, which might increase the photosynthetic area and production.